(untitled) (International Journal of Food and Nutritional Sciences, 2019)
This research explores the efficacy of utilizing Mobile Assisted Language Learning (MALL) in English as a Second Language (ESL) environments by executing a distinctive intervention program.Thirty ESL students participated in a six-month extensive MALL intervention aimed at enhancing their English language abilities. The intervention utilized carefully curated language learning apps, multimedia resources, and interactive exercises delivered through mobile devices. The research utilized a mixed-methods research approach, integrating both quantitative and qualitative methodologies for data collection..